EXPLORING MARINE GEOLOGY AND OCEANOGRAPHY IN MANGGAR WATERS: A PRELUDE TO THE BURGEONING BELITONG GEOPARK - F.X. Harkins H. Prabowo; Luli Gustiantini; Marina I. Siti; Fauzi Budi Prasetio; Yuli Yulianah; Catur Purwanto; Yusuf Adam Priohandono; Sonny Mawardi; Godwin Latuputty; Prisca Ayu Wastuwidyarani; Adi C. Sinaga; Swasty Aninda Piranti; Ferry Siboro; Agus Subekti; Sahudin Sahudin (Marine Geological Institute of Indonesia, 2023)
A survey on marine geology and oceanography was conducted in Manggar Waters, East Belitung, in order to protect the geological heritage of the newly inaugurated Belitong UNESCO Global Geopark (UGGp) in 2021. This study is aimed at understanding the characteristics of the seabed, marine sediments, currents, and coastal features in the area. A bathymetrical survey was done using an Echotrac echosounder to measure water depths, and current measurements were taken with an Infinity device. Forty sediment samples were collected and analyzed for their characteristics. The coastal features were examined through direct observation, and an unmanned aerial vehicle (UAV) drone was used to investigate the morphology of small islands. The results showed that the seabed was mainly composed of coarse sediments, such as sand and clayey sand, with some areas containing gravel near Buku Limau Island. The microfauna foraminifera analysis indicated a relatively low diversity, with Operculina and Amphistegina being the dominant species. Two types of beaches were recognized: the northern part, consisting of rocky beaches made of igneous rocks, and the southern part, which has flat beaches made of beach alluvium deposits. Abrasion was found to be dominant in the southern part, particularly at Tambak Beach. The study provides valuable information for the planning and management of marine areas in the Belitong Geopark. It also highlights the importance of preserving and protecting the geological heritage of the region. With this newfound knowledge, stakeholders can make cognizant decisions to ensure the conservation of the Belitong Geopark and its unique geological features.